2015
DOI: 10.1088/0031-9155/60/19/7461
|View full text |Cite
|
Sign up to set email alerts
|

Automatic liver contouring for radiotherapy treatment planning

Abstract: To develop automatic and efficient liver contouring software for planning 3D-CT and four-dimensional computed tomography (4D-CT) for application in clinical radiation therapy treatment planning systems.The algorithm comprises three steps for overcoming the challenge of similar intensities between the liver region and its surrounding tissues. First, the total variation model with the L1 norm (TV-L1), which has the characteristic of multi-scale decomposition and an edge-preserving property, is used for removing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Automation of these areas is also being addressed but have not been covered in this review. [197][198][199][200][201][202][203][204] Real-time interactive planning is a new paradigm for IMRT planning that is not based on using traditional optimisation algorithms. Instead, the goal is to be able to give the treatment planner the ability to perform real-time and interactive manipulation of the isodose or DVH lines and ultra-fast (automated) reoptimisation and dose estimation to update the user on the impact of interactive modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Automation of these areas is also being addressed but have not been covered in this review. [197][198][199][200][201][202][203][204] Real-time interactive planning is a new paradigm for IMRT planning that is not based on using traditional optimisation algorithms. Instead, the goal is to be able to give the treatment planner the ability to perform real-time and interactive manipulation of the isodose or DVH lines and ultra-fast (automated) reoptimisation and dose estimation to update the user on the impact of interactive modifications.…”
Section: Discussionmentioning
confidence: 99%
“…We have researched the deformable registration algorithm over the last few years 24, 25. We also researched automatic contouring based on segmentation for radiotherapy treatment planning 26, 27, 28. We found that intensity‐based deformable registration algorithms are susceptible to distorting tissues because the presence of inconsistent intensities between CT and CBCT could cause significant registration errors.…”
Section: Discussionmentioning
confidence: 99%
“…The details of different methods are given with pros and cons in the literature [ 3 , 4 ]. Various techniques have been suggested for the segmentation of a liver which are graph cut [ 5 , 6 ], level set [ 7 , 8 ], thresholding [ 9 ], and region growing [ 10 ]. Preventing under-segmentation and boundary leaks are the big issues in gray-level techniques where the intensity in different organs.…”
Section: Introductionmentioning
confidence: 99%